Teacher learning: dialogues between concepts and practices - Amrein, Guillermina; Bonadeo, Flavia S.; Carrión, Gisela; Piccoli, Ivana (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
This paper intends to examine the epistemological and methodological principles of the Practicum component in an initial teacher education programme and their practical realisation in the day-to-day decisions made by student-teachers. Our perspectives on language, learning, teaching and assessment are taken as a point of departure for the presentation of specific didactic projects, sequences and materials that seek to embody them. All the teaching experiences presented in the paper took place at urban state secondary schools.